Trends in the settlement of migrant workers in the context of social and economic processes in contemporary Russia - Zelenkov Mikhail Yuryevich (EDP Sciences, 2021)
The purpose of the article is to identify the basic trends in the settlement of migrant workers in the Russian Federation. The methodology of the research was based on the humanistic approach, which allowed focusing on the problems of labor migrants’ life activity and their search for value-based orientations. The systemic and comprehensive approach allowed identifying and substantiating the directions of the trends in the settlement of labor migrants by regions and districts of Russia. The comparative analysis of scientific works helped to identify the causes of settlement of labor migrants by place of their labor activity. Two identified opposing trends are the main results of the study. The first is dispersed settlement, which objectively promotes the integration process of representatives of immigrant ethnic groups into the urban environment of the area of residence, at the expense of a simultaneous weakening of intra-ethnic social ties and an increase in the depth and density of contacts with the local population. The second is the opposite trend – the self-isolation of immigrant groups within the framework of compact settlements, leading to the emergence of large ethnic diasporas of migrants in certain areas of the hosting country. The novelty of the study comes from an original approach to the identification and justification of migrants’ settlement trends in the socio-economic conditions of modern Russia.